Lumbar spondylodiscitis secondary to Enterobacter cloacae septicaemia after extracorporeal shock wave lithotripsy - Kamanli, A; Sahin, S; Kavuncu, V; Felek, S (British Med Journal Publ Group, 2001)
[Abstract Not Available]
Keywords: Spondylitis